Design and analysis of a stable AQM controller for network congestion control. (2018) - Bisoy, Sukant Kishoro; Pattnaik, Prasant Kumar; Pati, Bibudhendu; Panigrahi, Chhabi Rani
In this work, a stable active queue management (AQM) controller named SAQM is proposed to control the congestion in the network and improve the stability of the queue length at internet router. It is an integrated rate and queue-based AQM technique which is stable and robust under dynamic environment where a number of TCP connections, bottleneck bandwidth, round trip time (RTT), and target queue length keeps changing. The proposed AQM controller is implemented in NS2 network simulator. In this paper, the control theory is used for stability analysis of TCP/SAQM system and finally validated through MATLAB Simulink model. The simulation results show that the SAQM outperforms other existing AQM controllers in terms of achieving queue stability, less oscillatory with faster response and at the same time it responds quickly to traffic change.